RETELLING STORY USING VIDEO TO IMPROVE STUDENTS SPEAKING SKILL AT SMA NEGERI 5 TERNATE - Aldasari A. Sahafin; Roswita M. Aboe; Indri Widyasti Anwar (Cakrawala Bahasa, 2022)
The purpose of this study was to determine the extent to which storytelling using video in improving students' speaking skills at SMA Negeri 5 Ternate City. This study used a quantitative method with a t-test, with a sample of 20 students of grade ten students from class X-E. The instrument of this research was pretest and posttest to collect data. The results of this study indicate that the posttest average value is 70.05 higher than the pretest average value of 51.15. The results indicated that students average score of speaking skill were still low before researcher implemented retelling story technique. The t-test value of 12,857 is higher than the t-table value of 1,729 at a significance level ofÂ  0,05 with 19 degrees of freedom. This means that H1 is accepted and H0 is rejected. In conclusion, the use of retelling stories is effective for improving students' speaking skills at SMA Negeri 5 Ternate City.